ON DIFFERENCE Ja,b-STATISTICAL CONVERGENCE - Kandemir, Hacer Sengul; Aral, Nazlim Deniz; Et, Mikail (Amer Inst Mathematical Sciences-Aims, 2026)
In this study, we introduce different characterizations of Ja,b-statistically convergent sequences. Some properties of difference Ja,b-statistically convergent sequences are investigated. Also, we introduce Ja-statistically bounded sequences and difference Ja,b-statistically bounded sequences and investigate the relationship between these concepts.
Keywords: Statistical convergence; Ja,b-statistical convergence; power series method